Midwifery, an unnatural career choice for men? A qualitative study with male nurse students - Renberg, Heidi; Sommerseth, Eva; Johannessen, Aud (Nordisk Tidsskrift for Helseforskning, 2022)
Background: Many professions are gender divided. In Norway, there are only 22 male educated midwives out of 6711. Aim: To gain knowledge of male nursing students’ views of the reasons why few men become midwives. Method: This qualitative study collected data through focus-group interviews and individual interviews with male nursing students. Results: Three themes emerged from the analysis: midwifery is an unnatural career choice for men; men have little knowledge of the midwifery profession; to experience of demands and uncertainty associated with the education and profession. These themes included seven sub-themes. Conclusion: Midwifery as a career choice is constrained by the societal view of this career, which is considered a feminine occupation. The ‘midwife’ title can deter males from studying midwifery. Access to male role models is an important prerequisite for recruiting men, and it can be difficult for them to enter midwifery education and to obtain permanent employment after graduation. These results may contribute to less interest of the profession.